Elucidation of cold adaptation in Glaciimonas sp. PAMC28666 with special focus on trehalose biosynthesis - Shrestha, Prasansah; Karmacharya, Jayram; Han, So-Ra; Lee, Jun Hyuck; Oh, Tae-Jin (Frontiers in Microbiology, 2023)
The extremophilic bacterium Glaciimonas sp. PAMC28666, found in Antarctica soil belonging to Oxalobacteraceae family. It is the only complete genome of Glaciimonas in the NCBI database. Its genome measures 5.2 Mb and comprises 4476 genes (4350 protein-coding and 72 non-coding). Phylogenetic analysis shows the strain PAMC28666 in a unique branch within the genus Glaciimonas, closely related to Glaciimonas alpine Cr9-12, supported by robust bootstrap values. In addition, strain PAMC28666 showed 77.08% and 23.3% ANI and DDH respectively with Glaciimonas sp. PCH181. This study focuses on how polar strain PAMC28666 responds to freeze-thaw conditions, revealing a survival rate of 47.28% when subjected to 15 0 C for a period of 10 days. Notably, two genes known to be activated in response to cold, namely Trehalose 6phosphate synthase (otsA) and Trehalose 6-phosphate phosphatase (otsB), exhibited increased expression when the temperature shifted from 25 0 C to 15 0 C. This upregulation of otsAB and subsequent trehalose synthesis enhances the cold resistance of strain PAMC28666, providing insights into the relationship between trehalose production and adaptation to cold stress. Furthermore, studying this overlooked cold-adapted isolate like Glaciimonas sp. PAMC28666 could provide valuable insights into trehalose synthesis in cold-adapted environments.Additionally, there is potential to extract trehalose compounds from this strain for diverse biotechnological applications, including food and cosmetics, with ongoing research exploring its unique properties.